Is enhancing the professionalism of healthcare providers critical to tackling antimicrobial resistance in low- and middle-income countries? - Mishal S. Khan; Sothavireak Bory; Sonia Rego; Sovanthida Suy; Anna Durrance-Bagale; Zia Sultana; Sophea Chhorn; Socheata Phou; Chanra Prien; Sotheara Heng; Johanna Hanefeld; Rumina Hasan; et al. (BMC, 2020)
Abstract Background Healthcare providers' (HCPs) professionalism refers to their commitment and ability to respond to the health needs of the communities they serve and to act in the best interest of patients. Despite attention to increasing the number of HCPs in low- and middle-income countries (LMIC), the quality of professional education delivered to HCPs and their resulting professionalism has been neglected. The Global Action Plan on Antimicrobial Resistance (AMR) seeks to reduce inappropriate use of antibiotics by urging patients to access antibiotics only through qualified HCPs, on the premise that qualified HCPs will act as more responsible and competent gatekeepers of access to antibiotics than unqualified HCPs. Methods We investigate whether weaknesses in HCP professionalism result in boundaries between qualified HCPs and unqualified providers being blurred, and how these weaknesses impact inappropriate provision of antibiotics by HCPs in two LMIC with increasing AMR-Pakistan and Cambodia. We conducted 85 in-depth interviews with HCPs, policymakers, and pharmaceutical industry representatives. Our thematic analysis was based on a conceptual framework of four components of professionalism and focused on identifying recurring findings in both countries. Results Despite many cultural and sociodemographic differences between Cambodia and Pakistan, there was a consistent finding that the behaviour of many qualified HCPs did not reflect their professional education. Our analysis identified five areas in which strengthening HCP education could enhance professionalism and reduce the inappropriate use of antibiotics: updating curricula to better cover the need for appropriate use of antibiotics; imparting stronger communication skills to manage patient demand for medications; inculcating essential professional ethics; building skills required for effective collaboration between doctors, pharmacists, and lay HCPs; and ensuring access to (unbiased) continuing medical education. Conclusions In light of the weaknesses in HCP professionalism identified, we conclude that global guidelines urging patients to only seek care at qualified HCPs should consider whether HCP professional education is equipping them to act in the best interest of the patient and society. Our findings suggest that improvements to HCP professional education are needed urgently and that these should focus not only on the curriculum content and learning methods, but also on the social purpose of graduates.